Descrição Unificada dos Métodos Modernos para Estimação DOA em Arranjos de Sesnsores10.14209/jcis.2001.12 - F. Colares, Ricardo; A. Alves, Carlos; Lopes, Arnauri (Journal of Communication and Information Systems, 2015)
This work presents the most important direction of arrival (DOA) estimation methods proposed in the last two decades. In general, those methods are based on different concepts and properties rendering the comparisons among them a hard task. The aim of this paper is to present those methods in a unified formulation and notation to allow a direct comparison of their performance and computational effort. In addition, the paper also provides insights into the design of new methods.